Forms of post-modernism in performance of Iraqi theatre "dream of Baghdad exam": عمار عبد سلمان محمد (Al-Academy, 2021)
The effects of postmodernism on theatrical form was managed by the director (Anas Abdul Samad) to be employed in the Iraqi play (Dream in Baghdad) and the researcher sought to study this problem and divided it into four chapters dealt with in the first chapter the problem of research and its need, the importance of research, As well as the definition of terminology, either Chapter II theoretical framework divided by the researcher to the first two is the postmodernism in the theater is the most prominent reference references and the second most important postmodern applications in the world play and then the researcher concluded the second chapter of the most important indicators. In the third chapter, the researcher identified the research society and the method of selection of the sample (dream in Baghdad) and the analysis of the sample and concluded the most important results of the analysis of the sample, and the fourth chapter will lead the researcher the main findings of his research and conclusions reached by the researcher recommended a set of recommendations as well as proposals and list of sources and references